2003
DOI: 10.1023/b:myco.0000003606.13934.74
|View full text |Cite
|
Sign up to set email alerts
|

Do Trichothecenes Reduce Viability of Circulating Blood Cells and Modify Haemostasis Parameters?

Abstract: This manuscript describes the results of experiments conducted using human blood cells to determine the ability of T-2 toxin and DON to cause changes in clotting time, platelet aggregation, red blood cell haemolysis, RBC glucose content, lactate release, glutathione depletion, as well as white blood cell viability. In vitro results showed that haemostasis parameters and erythrocytes were not affected at concentrations able to induce inhibition of haematopoietic progenitor proliferation. In the presence of 10(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Proliferation was completely inhibited at 10 -8 M T-2 toxin ans 10 -7 M HT-2 toxin. In vitro investigations on the effects of T-2 toxin on haemostasis parameters and the viability of circulating blood cells revealed that haemostasis parameters and erythrocytes were not affected at concentrations (10 -5 and 10 -6 M) able to induce inhibition of heamatopoietic progenitor proliferation, indicating that haematopoietic progenitos appear more sensiitve to T-2 toxin than mature blood cells (Froquet et al, 2003).…”
Section: Observation In Human Cellsmentioning
confidence: 96%
“…Proliferation was completely inhibited at 10 -8 M T-2 toxin ans 10 -7 M HT-2 toxin. In vitro investigations on the effects of T-2 toxin on haemostasis parameters and the viability of circulating blood cells revealed that haemostasis parameters and erythrocytes were not affected at concentrations (10 -5 and 10 -6 M) able to induce inhibition of heamatopoietic progenitor proliferation, indicating that haematopoietic progenitos appear more sensiitve to T-2 toxin than mature blood cells (Froquet et al, 2003).…”
Section: Observation In Human Cellsmentioning
confidence: 96%
“…Selected studies from the previous evaluations and present studies are summarised in Tables 27 and 28. Froquet et al (2003) compared the sensitivity of human circulating blood cells to the sensitivity of human haematopoietic progenitors and some blood parameters. The authors showed that human haematopoietic progenitors are more sensitive to cytotoxic effects of T-2 toxin and concluded that haematological problems associated with T-2 toxin intoxication can be attributed to haematopoiesis inhibition.…”
Section: Haematotoxicity and Myelotoxicitymentioning
confidence: 99%
“…The concentrations tested were chosen according to previous studies (Lautraite et al, 1995Rio et al, 1997;Froquet et al, 2003) and were 0.1, 1, 10 and 100 nmol/L and 1 μmol/L for T-2 toxin (MW = 466.5); 1, 10, 100 nmol/L, and 2 μ mol/L for DON (MW = 296.3); 3.2, 32 and 320 nmol/L for domoic acid (MW = 311.3).…”
Section: Xenobiotic Assaysmentioning
confidence: 99%